Comprehensive validation of seven root zone soil moisture products at 1153 ground sites across China - Jing Tian; Yongqiang Zhang (International Journal of Digital Earth, 2023)
Root zone soil moisture (RZSM) is a critical parameter for drought monitoring, agriculture, and vegetation growth. In situ measurements of RZSM are scarce, and therefore, RZSM products are derived mainly through modeling approaches. This study evaluated seven RZSM products, including ERA5, MERRA2, CFSR, SMAP level 4, GLDAS-NOAH2.1, GLDAS-Catchment2.2, and SMOS CATDS Level 4, using 1153 ground sites across China. The evaluations aimed to address which products perform better, how well they capture the seasonal variations, and how they perform under different land surface and climate conditions. Results showed that MERRA2 and NOAH had the best performance, with MERRA2 having a better ability to capture surplus and deficit soil moisture conditions. The study also revealed that precipitation forcing plays a vital role in improving RZSM simulations. Conversely, ERA5 overestimates RZSM, and SMOS exhibits a dry bias. From the time series variability, all datasets except SMOS can capture the temporal dynamics of RZSM well. Moreover, the accuracy of the RZSM products varies significantly in tropical climate zones. This study provides crucial insights for improving land surface and hydrological models in estimating RZSM, which will help in drought management and agriculture production.